The box [videorecording (DVD)] - Linder, Doveed; Wassilak, David; Sanditz, Stephanie; MacArthy, Will; Heuvelman, Charles (Gravitas Ventures, 2024)
In the tradition of The Twilight Zone and Invasion of the Body Snatchers, this sci-fi anthology features four intertwining stories surrounding a mystical box. Bringing a fresh look to the imposter genre, humans are kept in a small metal box by inter-dimensional beings while their clones walk freely.